Doing Development Differently at the World Bank: updating the plumbing to fit the architecture - Bain, Katherine A.; Booth, David; Wild, Leni (ODI, 2016)
Keywords: IMPORTANT

The Radical How - Greenway, Andrew; Loosemore, Tom (Nesta and Public Digital, 2024)
Any mission-focused government should be well equipped to define, from day one, what outcomes it wants to bring about. But radically changing what the government does is only part of the challenge. We also need to change how government does things. The usual methods, we argue in this paper, are too prone to failure and delay. There’s a different approach to public service organisation, one based on multidisciplinary teams, starting with citizen needs, and scaling iteratively by testing assumptions. We’ve been arguing in favour of it for years now, and the more it gets used, the more we see success and timely delivery. We think taking a new approach makes it possible to shift government from an organisation of programmes and projects, to one of missions and services. It offers even constrained administrations an opportunity to improve their chances of delivering outcomes, reducing risk, saving money, and rebuilding public trust. The Radical How in a nutshell The struggles and shortcomings of delivering in government are well rehearsed. Many of the root causes that make it tough have been restated several times over several decades. But what to do? We believe the government can and should change how it delivers, by: organising around multidisciplinary teams embracing incremental, feedback-driven iteration focusing more on outcomes. The Radical How is a change of mindset as much as a change in organisation. It promotes methods and processes that have been shown to work, multiple times, at scale. They are the default ways of working for many of the world’s most successful companies. However, the occasions where they have been deployed are rare in government. These occasions have come about thanks to exceptional leaders, exceptional circumstances, or both. We think they’d make a big difference if they became the norm, rather than the exception. We also think that without them, mission oriented government will not become a reality. New policy ideas will remain just that, rather than translating into profound improvements to society. Central to this approach is the widespread adoption of internet-era ways of working. This paper explains both those and our thinking in more detail, with reference to real examples.

Making good on donors’ desire to Do Development Differently - Honig, Dan; Gulrajani, Nilima (Third World Quarterly, 2018)
AbstractForeign aid donors are increasingly focused on changing the way their development agencies function. This discourse has focused on desired qualities, including greater knowledge of local contextual realities, appropriate adaptation to context and greater flexibility to respond to changing circumstances. We argue that more attention needs to be devoted to the achievement of these qualities and turn to contingency theory to identify some under-exploited ways to ?do development differently?. The qualities sought by donors are emergent properties of complex organisational systems and will only be achieved through a micro-level and interlinked focus on the fundamentals of organisation.

Putting theory into practice: how DFID is doing development differently - Wild, Leni; Booth, David; Valters, Craig (ODI, 2017)
Keywords: IMPORTANT